Docagem molecular utilizando métodos semiempíricos quânticos - Costa, Antônio Luiz Silveira Vilanova (2019)
Human health is constantly affected by several diseases, needing a constant search for new drugs capable of combating these effectively. However, the cost associated with the development of a new drug can reach billions of dollars. As an alternative to reducing the high cost of the drug development process both industry and academia have increasingly invested in the application of computational methodologies, especially in the screening stage of potential lead compounds. Since the use of these computational tools indicates which chemical compounds have potential activity against a particular target thus reducing the number of compounds tested experimentally against the enzyme of interest. Computational studies have shown that the use of partial charges instead of Gasteiger's charges for both the ligand and the enzyme allow a more accurate estimation of the geometry of the protein-ligand complexes, thus improving the quality and reliability of molecular docking studies. The aim of this study was to evaluate the influence of the semiempirical charges to obtain the native conformation of a series of proteins of biological interest, as well as to investigate the influence of the cutting radius on the protein around the ligand molecule, both for the optimization of their geometry as well as for the replacement of Gasteiger charges by semiempirical charges. The optimization of the ligand in MOPAC was performed with the semiempirical methods AM1, PM3, PM6, PM6-D3, PM6-D3H4X, PM6-DH +, PM6-DH3X, PM7 and RM1, all protein residues evaluated and their waters crystallographic were fixed in their crystallographic positions. Only the ligand and hydrogens of the fixed molecules were optimized. An analysis of the RMSD of the ligand was carried out to investigate the influence of the size of the cutoff for the optimization of the geometry of the ligands. It was observed that the results showed that the systems did not exhibit major changes with the size of the active site, the 4 Å cutting radius being defined around the ligand as satisfactory for the optimization. For the substitution of the protein charges, the best results were obtained for systems in which the charges of all residues within 12 Å of the ligand molecule were substituted. The semiempirical charges presented results similar to those obtained for the Gasteiger charges, with the PM6 and Gasteiger methods being the that obtained a higher success rate in search of the native ligand conformation.